Protection of Ulayat Rights of Customary Law Communities in the Development of Food, Energy, and Water Self-Sufficiency Areas in South Papua - Muslim Lobubun (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The development of Food, Energy, and Water Self-Sufficiency Areas in South Papua may conflict with the ulayat rights of customary law communities that continue to exist and have been exercised across generations. This study aims to analyze the protection of ulayat rights and to formulate an appropriate legal protection model. It employs a normative legal research method using statutory, conceptual, and historical approaches. The findings indicate that ulayat rights are recognized under the Constitution, agrarian law, and Papua’s Special Autonomy framework, but their implementation continues to face challenges concerning territorial recognition, community consent, land use, and project oversight. Legal protection must therefore operate from the planning stage through restoration by incorporating the mapping of customary territories, community consent, legal certainty regarding land use, benefit-sharing, monitoring, dispute resolution, and environmental restoration. This model is necessary to ensure that development can proceed without severing the relationship between customary law communities and the land and natural resources that constitute their living territories.